Distribution, growth habit and morphological characteristics of Piper borneense N.E.Br. varieties in Sarawak, Malaysia - Lepun, Philip; Robin, Tunung; Alan, Ribka (AESS Publications, 2022)
Preserving and documenting ethnobotanical knowledge and plant use practices by ethnic groups is an urgent responsibility. This study aims to determine and document the ecological requirements and the distribution of Piper borneense varieties, their growth habits, and their morphological characteristics. This study was conducted in Belaga, Tatau and Bintulu, Sarawak, Malaysia. The plant samples were collected, Global Positioning System (GPS) readings and ecological conditions were recorded, and plant samples were analysed. Three different varieties were identified, and variety 1 was found to be widespread in the study area. The distribution of Piper species variety was greatly influenced by human activities and natural factors, while the growth habit was greatly influenced by soil's organic substrate, light intensity and soil moisture. Changes to forest environment area need to be monitored so that the growth of wild piper community and its growth habits are easily understood for sustainable forest management.